HISTORY AND TECHNOLOGICAL ASPECTS OF ANTIBIOTIC SENSITIVITY TESTING - V. V. Zverev; Yu. V. Nesvizhskiy; S. N. Mindlin; N. Yu. Tarasova (Сеченовский вестник, 2016)
The present article discusses a history and technological aspects of antibiotic susceptibility testing methods and indentiﬁes individual periods associated with the introduction of new technologies. The article demonstrates that the introduction of a diagnostic approach is associated with technological elaboration, standardization, the availability of appropriate equipment, qualiﬁed personnel, organizational structure and the international recognition, as well as medical and economic eﬃciency. “Noncultural” automated technologies seem to be promising for practical implementation. Meanwhile, the progressin this ﬁeld requires serious consideration of a number of technological and organizational issues, e.g. standardization and the proof of speciﬁcity.